2012
DOI: 10.1111/pan.12013
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric airway management: current practices and future directions

Abstract: Management of a pediatric airway can be a challenge, especially for the non-pediatric anesthesiologists. Structured algorithms for an unexpected difficult pediatric airway have been missing so far. A recent step wise algorithm, based on the Difficult Airway society (DAS) adult protocol, is a step in the right direction. There have been some exciting advances in development of pediatric extra-glottic devices for maintaining ventilation, and introduction of pediatric versions of new 'non line of sight' laryngosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(67 citation statements)
references
References 57 publications
0
66
0
1
Order By: Relevance
“…2 Dans la plupart des centres, l'incidence la plus élevée est observée chez les nourrissons (moins d'un an) 3 et les patients atteints d'anomalies cardiaques congénitales. 4 Dans une étude unicentrique récente, l'incidence de laryngoscopie difficile était de 0,68 %, les nourrissons de moins d'un an et les adolescents présentant des anomalies cranio-faciales représentant la majorité des cas.…”
Section: Comment Prévoir Les Difficultés De Prise En Charge Des Voiesunclassified
See 2 more Smart Citations
“…2 Dans la plupart des centres, l'incidence la plus élevée est observée chez les nourrissons (moins d'un an) 3 et les patients atteints d'anomalies cardiaques congénitales. 4 Dans une étude unicentrique récente, l'incidence de laryngoscopie difficile était de 0,68 %, les nourrissons de moins d'un an et les adolescents présentant des anomalies cranio-faciales représentant la majorité des cas.…”
Section: Comment Prévoir Les Difficultés De Prise En Charge Des Voiesunclassified
“…2 In most centres, the incidence is highest in the infant age group (less than one year of age) 3 and in patients with congenital cardiac anomalies. 4 In a recent single-centre study, the incidence of difficult laryngoscopy was found to be 0.68%, with infants under one year of age and teenagers with craniofacial anomalies representing the majority of cases.…”
Section: Predicting Difficulty In Pediatric Airway Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, management of a pediatric airway can be a challenge, especially for anesthesia providers with limited pediatric experience, who may find the normal airways of younger children difficult to manage. So far, there is no structured algorithms for an unexpected difficult pediatric airway (8) and Airtraq) versus direct laryngoscope demonstrates that videolaryngoscopes are associated with improved laryngeal views in children either with normal airways or with potentially difficult airways. With videolaryngoscopes, however, the intubation time is prolonged and the incidence of failed intubation is increased significantly (11).…”
Section: Ideal Airway Management: New Evidence and Strategies Are Stimentioning
confidence: 99%
“…In addition, these devices may be useful when difficulties with mask ventilation and/or tracheal intubation are encountered [5,6], supporting their inclusion as rescue devices in difficult airway algorithms [7][8][9]. In the paediatric population, children under the age of one year have been reported to have the highest incidence of difficult airway [10,11].…”
Section: Introductionmentioning
confidence: 99%